Perioperative "stress dose" of corticosteroid: Pharmacological and clinical perspective - Geetanjali T Chilkoti; Anshul Singh; Medha Mohta; Ashok Kumar Saxena (Wolters Kluwer Medknow Publications, 2019)
Various exogenous steroid preparations have been in use for a wide range of indications. We, as an anesthesiologist often encounters a surgical patient receiving chronic steroid therapy. Perioperative use of steroid is associated with major complications such as full-blown adrenal crisis in the perioperative period due to the secondary adrenal insufficiency. Henceforth, comes the role of the perioperative "stress-dose" of steroids to mitigate this rare but potentially fatal complication. There have been opposing views regarding the need and the appropriate dosage of the perioperative steroids. The present review discusses the changing concept of perioperative "stress dose" of corticosteroids, its pharmacokinetics, clinical relevance, and the related controversies such as the need and the appropriate dose.